Science communication and outreach with music from plants and phytoacoustics - Carmelo Cannarella (Science, Technology, and Communication Journal, 2025)
Integrating innovative methods in scientific communication is essential to stimulate interest in science in particular in children and young people. Music originated from electric conductivity (EC) of plants seems to be an effective tool for translating complex scientific concepts into simple and engaging sensory experiences and to underline the potential of music for sustainability transformation. Plant-generated music, through immersive sound experiences and promoting active learning, makes scientific concepts more accessible stimulating curiosity, motivation and interest in scientific research and environmental issues. Many studies confirmed the effectiveness of non-formal approaches in science dissemination and the experiences made at the Institute for Biological Systems of the National Research Council of Italy (CNR-ISB) highlight how music generated from EC of plants and phytoacoustics may encourage scientific and sustainability awareness and a multidisciplinary vision of natural sciences.